Estrategia de distribución del pisco peruano en el mercado de Estados Unidos: el caso de Texas - Lama, Natali (2007)
In this piece, the distribution channels for pisco –Peruvian first press grape brandy– in the United States liquor market are evaluated in order to design entry and commercialization strategies for this product, focusing specifically on the state of Texas. To meet this objective, studies are conducted for the size of the spirited drinks market, the characteristics and trends of consumption, the size and characteristics of the export supply, commercialization strategies being used by current exporters, as well as legal and tax considerations that regulate the commercialization of liquor in the US. Finally, the distribution chain is analyzed, from the costs structure to the benefits and margins per participant. The investigation covered statistical data, field investigations for destination markets, interviews with American experts, product testing and pattern studies on the behavior of exporters’ clusters, among other aspects.